What's the harm in asking? A systematic review and meta-analysis on the risks of asking about suicide-related behaviors and self-harm with quality appraisal. Issue 2 (3rd April 2022) - Polihronis, Christine; Cloutier, Paula; Kaur, Jaskiran; Skinner, Robin; Cappelli, Mario
Abstract: Research emphasizes the importance of asking about suicidality. Unfortunately, misperceptions of harm remain which can compromise clinical care, research, and public health surveillance efforts. Our objective was to evaluate the empirical evidence on whether and how asking about suicide related behaviors (SRB), such as suicidal ideation and suicide attempts, and non-suicidal self-injury (NSSI) results in harmful outcomes. We reviewed and rated seventeen studies and conducted a systematic review and random-effects meta-analysis on eight studies comparing those asked vs. not asked on immediate and later SRB, NSSI, and psychological distress (PD). Forest plots demonstrated no statistically significant effects of asking on SRB, NSSI, or PD. Eight RCTs provided the strongest evidence and demonstrated either low or unclear risk of bias, and the remaining cohort studies were of low to moderate quality. With the current available evidence, we found no harmful outcomes of asking, however more RCTs with a low risk of bias are required to firmly conclude that asking through self-report and interview methods does not further exacerbate distress, SRB and NSSI compared to those not asked.